2012
DOI: 10.2108/zsj.29.690
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression Profile of Sex-Specific Genes, Figla and Dmrt1, in the Protogynous Hermaphroditic Fish, Halichoeres Poecilopterus

Abstract: The genes folliculogenesis specific basic helix-loop-helix (facor in the germline alpha, Figla) and doublesex and mab-3 related transcription factor 1 (Dmrt1) are female- and male-specific genes that play key roles in sex differentiation. To obtain a better understanding of the molecular mechanisms underlying female-to-male sex change, we cloned the cDNAs of these genes from an ovary and a testis of the protogynus wrasse, Halichoeres poecilopterus. This fish has two isoforms of Dmrt1, Dmrt1a and Dmrt1b, caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 103 publications
(120 reference statements)
1
18
0
Order By: Relevance
“…This transcription factor up-regulates ZP genes, which code for products used to build the vitelline envelope surrounding eggs in teleosts (zona matrix) 76 – 78 . Moreover, it has been suggested that the Figla factor displays an anti-parallel direction of expression to Dmrt1 during the transition from male to female in a protandrous 79 and vice versa in a protogynous teleosts 80 . The same expression pattern was showed for Foxl2 , a prominent marker of ovarian development across vertebrates 81 .…”
Section: Discussionmentioning
confidence: 99%
“…This transcription factor up-regulates ZP genes, which code for products used to build the vitelline envelope surrounding eggs in teleosts (zona matrix) 76 – 78 . Moreover, it has been suggested that the Figla factor displays an anti-parallel direction of expression to Dmrt1 during the transition from male to female in a protandrous 79 and vice versa in a protogynous teleosts 80 . The same expression pattern was showed for Foxl2 , a prominent marker of ovarian development across vertebrates 81 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the rapid decreases in the male-related genes, our results demonstrate that the female-related genes ( figla , foxl2 , and cyp19a1a ) were gradually increased (but not rapidly) after AI/MT-termination. In fish, figla is a female marker expressed in the ovary [ 24 , 46 ]. In addition, black porgy figla /Figla existed only in oocytes, but not oogonia [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In trying to understand the molecular control of sex change in sequential hermaphrodites, gene expression studies have focussed on these core genes and their potential proximate regulators. Most work has focussed on the protandrous black porgy [Wu and Chang, 2009;Wu et al, 2010aWu et al, , b, 2012Wu et al, , 2015 and on protogynous wrasse and grouper [Li et al, 2006;Xia et al, 2007;Alam et al, 2008;Liu et al, 2009;Kobayashi et al, 2010b;Miyake et al, 2012;Horiguchi et al, 2013;. Recently, and for the first time, whole-transcriptome expression analysis was used to comprehensively examine how expression landscapes alter across natural sex change in brain and gonad tissues of the protogynous bluehead wrasse [Liu, 2016].…”
Section: Molecular Regulation Of Sex Change: Switches Triggers and mentioning
confidence: 99%